2015
DOI: 10.1002/nvsm.1529
|View full text |Cite
|
Sign up to set email alerts
|

The timing of final charitable bequest decisions

Abstract: Understanding the timing of final charitable bequest decisions permits nonprofits to co‐ordinate their marketing efforts to correspond with donor decision‐making. Using probate data from Australia and longitudinal survey data from the USA, this paper seeks to identify the timing of decisions that resulted in realized charitable bequests. We find evidence that charitable transfers result mostly from decisions that occur during the last 5 years of life and at the oldest ages. Charitable plans made earlier in lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Distinct campaigns centred on positive attitudes towards military charities and emergency services charities will resonate here. The older age of this cluster links clearly with research undertaken on charitable bequests such as James III and Baker (2015), who identified from US and Australian data levels of end-of-life donations formalised within estate plans. This segment may be worth targeting with bequest solicitations on entering retirement age.…”
Section: Implications Of Four Donor Segmentssupporting
confidence: 59%
“…Distinct campaigns centred on positive attitudes towards military charities and emergency services charities will resonate here. The older age of this cluster links clearly with research undertaken on charitable bequests such as James III and Baker (2015), who identified from US and Australian data levels of end-of-life donations formalised within estate plans. This segment may be worth targeting with bequest solicitations on entering retirement age.…”
Section: Implications Of Four Donor Segmentssupporting
confidence: 59%
“…), and the median age category was the 30s. Because of the particular importance of the bequest decision making of older adults (James and Baker, ), the statistical analysis includes separate interactions to examine the difference in effects of the messages on those aged 50 and above.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond this, the fluidity of such plans determines the relative importance of getting in the plan (initial commitment) and staying in the plan (retention), and thus the corresponding resources that should reasonably be assigned to each task. Although fundraising practitioners might prefer to work under the assumption that older decedents infrequently change their wills, previous research suggests otherwise (James III & Baker, 2015). Some evidence suggests that charitable bequest gift decisions that actually control estate transfers are made late in life.…”
Section: Introductionmentioning
confidence: 99%
“…Further, over three-fourths of bequest dollars transferred to charity were from wills signed at age 80 or older (James III & Baker, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation